The two towers : being the second part of The lord of the rings. - Tolkien, J. R. R. (John Ronald Reuel), 1892-1973 (Tolkien, J. R. R. (John Ronald Reuel), 1892-1973. Lord of the rings, 1965)
The second volume of The lord of the rings epic, set in the fantastic world of the Third Age of Middle-earth.